Prevalence and clinical profile of chronic pain and its association with mental disorders - Flávia Garcia Pereira; Mariane Henriques França; Maria Cristina Alochio de Paiva; Laura Helena Andrade; Maria Carmen Viana (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To identify the prevalence of 12-month self-reported pain and chronic pain in a general population and to describe their clinical profile to assess if chronic pain is associated with 12-month mental disorders. METHODS The data used comes from the São Paulo Megacity Mental Health Survey, a population-based study assessing adult (≥ 18 years) residents of the São Paulo metropolitan area, Brazil. We have assessed the respondents (n = 5,037) using the Composite International Diagnostic Interview (CIDI 3.0), with a global response rate of 81.3%. Descriptive analyses have been performed, and crude and adjusted odds ratios (OR) have been calculated with logistic and multinomial regression and presented with respective 95% confidence intervals (95%CI). RESULTS The prevalence of pain and chronic pain in the past 12 months were 52.6% (95%CI 50.3-54.8) and 31.0% (95%CI 29.2-32.7), respectively. Joints (16.5%, 95%CI 15.4-17.5) and back or neck (15.5%, 95%CI 14.2-16.9) were the most frequently reported anatomical sites of chronic pain. On a 10-point analogue scale, the mean intensity of the worst pain was 7.7 (95%CI 7.4-7.8), and the mean average pain was 5.5 (95%CI 5.2-5.6); the mean treatment response was 6.3 (95%CI 6.0-6.6). Mean pain duration was 16.1 (95%CI 15.6-17.0) days a month and 132 (95%CI 126-144) minutes a day. Chronic pain was associated with 12-month DSM-IV mental disorders (OR = 2.7, 95%CI 2.3-3.3), anxiety disorders (OR = 2.1, 95%CI 1.9-3.0), and mood disorders (OR = 3.3, 95%CI 2.4-4.1). CONCLUSIONS A high prevalence of chronic pain in multiple sites is observed among the general adult population, and associations between chronic pain and mental disorders are frequent.